Patient Views of Behavioral Health Providers in Primary Care: A Qualitative Study of 2 Southeastern Clinics. (August 2020) - Koehler, Aubry N; Trejo, Grisel; Sandberg, Joanne C; Swain, Brittany H; Marion, Gail S; Kirk, Julienne K
Background: Limited research is available around patient experience of integrated behavioral health care in primary care settings. Objective: We sought to identify the major themes through which patients described their integrated behavioral health care experiences as a means of informing and improving clinic processes of integrated health care delivery. Methods: We captured viewpoints from 16 patients who experienced an integrated behavioral health care model from 2 primary care clinics and completed at least 3 visits with a behavioral health provider (BHP). Using grounded theory analyses, we coded and analyzed transcriptions for emergent themes. Analysis: The interview process yielded 3 major themes related to the BHP including (a) the BHPs' clinic presence made behavioral health care more convenient and accessible, (b) BHPs worked within time and program limitations, and (c) BHPs helped with coping, wellness, and patient-care team communication. Conclusion: The BHPs serving in a large primary care practice and a Federally Qualified Health Center played an important role in connecting patients with behavioral health care and improving care team collaboration, both in terms of communication within the team and between the team and the patient/family.